'There’s no media for refugees': Information and communication in camps on the Thai-Burma border - Victoria Jack (Asia Pacific Network, 2017)
This article uses the example of camps on the Thai-Burma border to highlight the exclusion of refugees from the common world and subsequent omission of their voices from news coverage. Moreover, the article argues that this exclusion weakens the supposed protection offered to refugees by impeding the media in its role as protector and promoter of human rights. While there has been considerable literature examining the reporting of humanitarian crises to a global audience, in contrast there has been little in the way of research—and practice—concerning strategies to effectively communicate with refugees affected by such crises. Fieldwork conducted in three of nine official Thai-Burma border camps involved interviews with 81 participants, including refugees, humanitarian practitioners and journalists. Participant accounts show that a range of factors inhibit the production of news media coverage relevant to refugees interned in the Thai-Burma border camps, thereby preventing refugees from accessing vital information and voicing in common public space their experiences of violence, corruption and discrimination. A handful of exiled media groups provide poorly funded exceptions.